2022
DOI: 10.1159/000526002
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Vascular Fraction Reverses the Age-Related Impairment in Revascularization following Injury

Abstract: Adipose-derived stromal vascular fraction (SVF) has emerged as a potential regenerative therapy, but few studies utilize SVF in a setting of advanced age. Additionally, the specific cell population in SVF providing therapeutic benefit is unknown. We hypothesized that aging would alter the composition of cell populations present in SVF and its ability to promote angiogenesis following injury, a mechanism that is T cell-mediated. SVF isolated from young and old Fischer 344 rats was examined with flow cytometry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…After removing duplicates and screening titles and abstracts, 84 full-text articles were assessed for eligibility. Of these, 16 articles met the inclusion criteria and were included in the review (Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The selected studies included prospective and/or retrospective case series, randomized controlled clinical trials, and reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and screening titles and abstracts, 84 full-text articles were assessed for eligibility. Of these, 16 articles met the inclusion criteria and were included in the review (Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The selected studies included prospective and/or retrospective case series, randomized controlled clinical trials, and reviews.…”
Section: Resultsmentioning
confidence: 99%
“…The study demonstrated that tissue-engineered dermis grafts incorporating SVF yielded superior scar quality in the alar zone of the nose compared to traditional artificial dermis grafts. This finding is significant as it highlights SVF's potential in improving aesthetic outcomes in reconstructive surgery, offering more effective solutions for challenging areas like nasal defects [19,21]. Jeon et al [24] reported increased fat graft survival rates in breast reconstruction with SVF.…”
Section: Gulyaeva Et Al 2019mentioning
confidence: 94%